Depicting the composition of gut microbiota in a population with varied ethnic origins but shared geography. (October 2018) - Deschasaux, Mélanie; Bouter, Kristien; Prodan, Andrei; Levin, Evgeni; Groen, Albert; Herrema, Hilde; Tremaroli, Valentina; Bakker, Guido; Attaye, Ilias; Pinto-Sietsma, Sara-Joan; Raalte, Daniel; Snijder, Marieke; et al.
Abstract Trillions of microorganisms inhabit the human gut and are regarded as potential key factors for health1, 2 . Characteristics such as diet, lifestyle, or genetics can shape the composition of the gut microbiota2–6 and are usually shared by individuals from comparable ethnic origin. So far, most studies assessing how ethnicity relates to the intestinal microbiota compared small groups living at separate geographical locations7–10 . Using fecal 16S ribosomal RNA gene sequencing in 2, 084 participants of the Healthy Life in an Urban Setting (HELIUS) study11, 12, we show that individuals living in the same city tend to share similar gut microbiota characteristics with others of their ethnic background. Ethnicity contributed to explain the interindividual dissimilarities in gut microbiota composition, with three main poles primarily characterized by operational taxonomic units (OTUs) classified asPrevotella (Moroccans, Turks, Ghanaians), Bacteroides (African Surinamese, South-Asian Surinamese), and Clostridiales (Dutch). The Dutch exhibited the greatest gut microbiota α-diversity and the South-Asian Surinamese the smallest, with corresponding enrichment or depletion in numerous OTUs. Ethnic differences in α-diversity and interindividual dissimilarities were independent of metabolic health and only partly explained by ethnic-related characteristics including sociodemographic, lifestyle, or diet factors. Hence, the ethnic origin of individuals may be an important factor to consider in microbiome research and its potential future applications in ethnic-diverse societies. Stool microbiota composition correlates with the ethnic backgrounds of people living in the same city, suggesting that geographical location and ethnicity have distinct effects on microbiota.